Isolation and identification of blast disease on aerobic and anaerobic rice / Muhamad Norhisyam Nording - Nording, Muhamad Norhisyam (Faculty of Plantation and Agrotechnology, 2018)
Blast (Pyricularia oryzae) disease is one of the most major problems in the rice field. This research was done to isolate and identified the blast disease of rice that was attacked on aerobic and anaerobic rice. For the sampling, the anaerobic rice (MR220 CL2) was randomly sampled from rice cultivation area in Parit Penghulu (Melaka) and Kuala Rompin (Pahang) for aerobic rice (MRI A1). Isolation of fungal pathogen were done from leaves of rice plants by using surface sterilization isolation of tissues on PDA and incubated at room temperature at 28 ºC ± and examined daily for seven days. The identification of isolated fungal pathogen was identified based on cultural and morphological characteristics from isolates of anaerobic rice that were named as BD 1, BD 2, BD 3, BD 4, BD 5, BD 6, BD 7, BD 8, BD 10, BD 11 and aerobic rice was named as BDA 1 and BDA 2.The media that was used to growth fungal pathogen Pyricularia oryzae for aerobic and anaerobic rice is Potato Dextrose Agar (PDA). The observation of colonies characteristic such as color, margin, pigmentation, surface texture, mycelia growth and sporulation. Lacthopenol cotton blue was used to observe the conidial characteristic based on shape, base characteristic, apex characteristic and septation of conidial from both isolation. The results showed that rice blast is the most serious disease that was attacked on aerobic and anaerobic rice in Malaysia.